Notes on Changes in the Distribution of Manufacturing Wage Earners by Straight-Time Hourly Earnings, 1941-48 - Meyers, Frederic (The Review of Economics and Statistics, 1950)
C ONSIDERABLE attention has been given of recent years to changes in the pattern of wage relationships within and between industries. Among the more recent observations in this area is that of David R. Roberts.' Mr. Roberts, on the basis of measurements of changes in straight-time hourly earnings between major industry groups concludes, regulation of wages led to a narrowing of wage differentials between industries, between firms in the same industry, and between different classes of work in the same plant. Such effects have been more than temporary. Developments since V-J Day indicate that much of this wartime heritage has become a permanent ingredient of our economy. While the rate of reduction in differentials has been considerably slowed down, the trend in that direction still persists. 2 These observations are consistent with the general view. However, a study of distributions of wage earners within manufacturing industry by straight-time earnings, rather than comparisons of changes in distributions of averages between industry groups, leads to the conclusion that the trend toward lesser dispersion has not been substantially slowed down since the War. Table i presents the available distributions from January I94I to July I947.3 Exact statistical comparisons of the distributions are difficult because of the fact that all of them are open-end distributions, and arithmetic means are neither available nor calculable. Published data on average straight-time hourly earnings are not particularly useful since the samples are different. Several rough measures of the changes in the shape of the distributions have, however, been